KEWENANGAN PEMERINTAH DAERAH DALAM PEMBINAAN ATLET KARATE DI PROVINSI RIAU TAHUN 2014 - Aryuni Sadewi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The development of sport recently changes along with the changes in legislationgoverning regional autonomy and regulation about sport.Karate coaching in Riau Province is done in various forms such as athletes nursery,and the provision of facilities and infrastructure. Government authority in coaching karateathletes are handled directly by FORKI ( Federation of Indonesian Karate) as an organizationthat became the container sport karate, KONI ( Indonesian National Sports Committee) as thecenre of Youth and Sports ) as the agency government (an arm of the central government )that is sprcifically in charge of youth and sports.Coaching karate athletes in the Province of Riau still not going so well, we can seefrom the low achievement Riau Province karate athletes who are less able to compete withkarate athletes from other provinces invarious national championships, still lackinfrastructure and facilities to practice.Keywords: authority, coaching, sports, achievement, facilities, infrastructure